Nursing coaching leadership and its influence on job satisfaction and patient safety - Moraes, Márcia Cristina Souza de; Dutra, Gabrielle Oliveira; Ferreira, Thelen Daiana Mendonça; Dias, Flávia Carvalho Pena; Balsanelli, Alexandre Pazetto; Gasparino, Renata Cristina (Revista da Escola de Enfermagem da USP, 2021)
Objective: To compare the nursing technicians’ perception with the nurses’ self-perception of the exercise of nurses’ coaching leadership and to check the influence of this leadership model on the safety climate and on the team’s satisfaction. Method: This is a correlational study, carried out with 85 nurses and 85 nursing technicians, using the Questionnaire on the Nurse’s Self-Perception of Leadership Exercise, the Questionnaire on Nursing Technicians’ and Assistants’ Perception of Leadership Exercise, and the subscales Safety climate and Satisfaction at Work. The relations among the professionals’ responses were assessed using the Mann Whitney test and Spearman’s coefficient. Results: Nurses achieved higher means in the four dimensions of coaching Leadership, and in three, the differences were significant (p < 0.05). The dimensions of Coaching Leadership obtained positive and significant correlations with the subscales Safety Climate and Satisfaction, the majority being of moderate magnitude. Conclusion: Nurses’ self-perception regarding the exercise of leadership was more positive than the technicians’ assessment. The more the nurse exercises the dimensions of Coaching Leadership, the better the team’s safety climate and satisfaction.